Teori Modalitas sebagai Materi Pembelajaran Bahasa Indonesia - Abdurahman . (Fakultas Bahasa dan Seni UNP, 2011)
This article aims to explain the modalities in the Indonesian language as a material in language teaching. Modalities are the elements that are used by the speakers to express their attitude. Thus in language learning, the forms and the usage associated with the modalities need to be taught with the right strategies to students. Kata kunci: modalitas, bahasa Indonesia, pembelajaran